KEBIJAKAN PEMERINTAH TERHADAP TRADEOFF INFLASI DAN PENGANGGURAN : PERSPEKTIF EKONOMI ISLAM - Amalia Nuril Hidayati; Dwika Permata Sari; Via Aprillia Nanda Lestari; Muhammad Nada Choiruddin; Adinda Desi Rahmawati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstract. This study aims to analyze government policies on the tradeoff between inflation and unemployment using an Islamic economic perspective. Inflation and unemployment are major problems in the economy that are interrelated and often cause tradeoffs, so researchers examine how government policies can overcome these tradeoffs by considering Islamic economic principles. This study uses a library research method with a descriptive analytical and interpretative approach based on academic literature. The results of the study indicate that the implementation of government policies in overcoming the tradeoff between inflation and unemployment from an Islamic economic perspective must be based on the principles of social justice and fair distribution of wealth. Empirically, fiscal and monetary policies packaged with the principle of justice can effectively suppress inflation while reducing unemployment. In addition, social empowerment and efforts to improve community welfare are important factors in creating sustainable economic stability.